EFFECTS OF, ATMOSPHERIC HUMIDITY ON DEVELOPING EGGS OF AK GRASSHOPPER, Poekilocerus pictUs (Acridoidea Pyrgomorphidae), AN ARID ZONE SPECIES.
Eggs of Poekilocerus pictus at four developmental stages, viz , _(A) freslaly laid, (B) at germ-band formation, (C) at blastokinesis (c. halfdeveloped) and (D) at postblastokinesis (c. two-thirds developed), were kept at six constant atmospheric humidities (50,60,70,80,90 and 100% R;H.) and at a constant temperature of 31°± 1°C. The nurnidities were controlled in desiccators by various, dilutions of sulphuric acid in water. Freshly laid eggs did not develop at all they shrivelled arid died. The other three stages (B-D